TRACE ELEMENT PARTITIONING BETWEEN BADDELEYITE AND CARBONATITE MELT AT HIGH PRESSURES AND HIGH TEMPERATURES - Klemme S.; Meyer H.-P. (My University, 2003)
Baddeleyite (ZrO2) is an accessory phase in a wide range of rocks ranging from kimberlites to carbonatites. Despite an increasing interest in baddeleyite especially in the fields of geochronology and petrology, there is, however, no experimental information as to how trace elements partition between baddeleyite and silicate or carbonate melts. To address this problem, hitherto unknown partition coefficients between baddeleyite and carbonatite melt were determined experimentally at high pressures and high temperatures. Experimental run products were analysed for trace elements with secondary ion mass spectrometry and with the electron microprobe. Calculated partition coefficients indicate that U, Th, Hf, Nb and Ta as well as the heavy rare earth elements (HREE) prefer to enter baddeleyite rather than carbonate melts (D>1), whereas the light rare earth elements (LREE) and other trace elements behave incompatibly (D<1), i.e., they prefer to enter the carbonate melt rather than the baddeleyite crystal. The partition coefficients indicate that baddeleyite may be able to slightly fractionate Zr from Hf during fractional crystallisation of a carbonatite magma (DZr/DHf=1.4). Moreover, baddeleyite could fractionate U from Th during fractional crystallisation, in a similar manner to garnet.
Keywords: Baddeleyite